Clathrin Adaptor AP-2 Is Essential for Early Embryonal Development - Mitsunari, Takashi (American Society for Microbiology, 2005)
The heterotetrameric adaptor protein (AP) complexes AP-1, AP-2, AP-3, and AP-4 play key roles in transport vesicle formation and cargo sorting in post-Golgi trafficking pathways. Studies on cultured mammalian cells have shown that AP-2 mediates rapid endocytosis of a subset of plasma membrane receptors. To determine whether this function is essential in the context of a whole mammalian organism, we carried out targeted disruption of the gene encoding the μ2 subunit of AP-2 in the mouse. We found that μ2 heterozygous mutant mice were viable and had an apparently normal phenotype. In contrast, no μ2 homozygous mutant embryos were identified among blastocysts from intercrossed heterozygotes, indicating that μ2-deficient embryos die before day 3.5 postcoitus (E3.5). These results indicate that AP-2 is indispensable for early embryonic development, which might be due to its requirement for cell viability.